#TITLE_ALTERNATIVE# - (NIM 230 03 023); Pembimbing : Dr. Danu Ariono, YENNI
Solid-liquid adsorption is one of the separation processes that involve mass transfer of solute from liquid phase to solid phase. Solid-liquid adsorption process in this research is conducted in a percolation process. It means solvent containing solute flow slowly through into the grained solid stacked into the fixed bed. When the solvent containing solute contact with adsorbent, it is happening mass transfer of solute from solvent to adsorbent surface, so that solute concentration in solvent and in adsorbent will be changed toward time and its position in adsorption column. The performance of this process depends on the process dynamic inside the adsorption column. The purpose of this research is to build a model based upon percolation theory that can represent the solid-liquid adsorption dynamic process. This purpose is achieved by building a mathematical model and implementation experiment in laboratory. The model is then tested by adsorption methylene blue as solute carried water as solvent, with activated carbon as adsorbent. The experiment is conducted with variation of feed concentration (0.03-0.05 grit), feed flow rate (6-8ml/s) and size adsorbent (mesh -12+24 and mesh-6+12). Results of testing equilibrium model show that this model is close to reality experiment using size adsorbent smaller (mesh -12+24). It shows that in this adsorption process, it is happening equilibrium at the moment. between solute concentrations in liquid phase with in solid phase (at its surface) at every point in adsorption column (diffusion happens quickly). Non-equilibrium model with film diffusion, after is corrected, is resulting breakthrough curve is close to reality experiment using size adsorbent bigger (mesh -6+12). It shows that in this adsorption process, it is not happening equilibrium at the moment, but mass transfer of solute from solvent to solid experience film diffusion at activated carbon surface before gets its equilibrium. Correction factor is timed to feed concentration (m variable without dimension x0) that the value closes to effluent concentration at the end of adsorption process. Breakthrough curve will be slope slightly and parameter K (separation factor) increasing with feed flow rate decreasing, feed concentration decreasing and at the process adsorption using size adsorbent bigger.